(3JMbjb ePgH GdUhajIs - (3fhQ GdOjf YHO GdQMef Hf CMeO Hf eMeO GdLGej GdfbTHfOj, GdLGej,J (B898 (3g` s ((3eMeO SYjO Hf YHO GdZfi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi JLdi HPGJg dPGJg hHYO agPg QSGdI ai JMbjb ePgH GdUhajI hGdeJcdejf hGdMceGA GdeJbOejf hJbQjQ bhdge ai hLhH GdhGLH dPGJg s
(3BNQgG (B:s
(3hEeJfGY GdJNda HbOQI jNdbgG Gddg ai GdYHO EPG bGQfJ MUhd GdTQGFW hEQJaGY GdehGfY bO JeJ GdQSGdI GdTQjaI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B67s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ , RNGQa s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs